Neurosensory Disturbances after Sagittal Ramus Osteotomy - Corputty Johan Edwin Michael; J. P. Richard Van Merkesteyn (Journal of Dentistry Indonesia, 2015)
Permanent neurosensory disturbance of the inferior alveolar nerve is one of the most frequently occurring complications of the sagittal ramus osteotomy. Many authors have reported on this complication but the incidence differs widely. In this article of 25 patients who underwent a bilateral sagittal ramus osteotomy with the use of sagittal split separators and rigid transbuccal screw fixation, is reported. The incidence of permanent neurosensory disturbances appeared to be only 8%.